Cholinergic and glutamatergic transmission at synapses between pedunculopotine tegmental nucleus axonal terminals and A7 catecholamine cell group noradrenergic neurons in the rat. (November 2016) - Li, Meng-Jiyuan; Chang, Tien-Wei; Hung, Wei-Chen; Wu, Chieh-Yi; Luo, Yu-Cheng; Chang, Ting-Hsuan; Lin, Chingju; Yang, Chi-Sheng; Yang, Hsiu-Wen; Min, Ming-Yuan
Abstract: We characterized transmission from the pedunculopotine tegmental nucleus (PPTg), which contains cholinergic and glutamatergic neurons, at synapses with noradrenergic (NAergic) A7 neurons. Injection of an anterograde neuronal tracer, biotinylated-dextran amine, into the PPTg resulted in labeling of axonal terminals making synaptic connection with NAergic A7 neurons. Consistent with this, extracellular stimulation using a train of 10 pulses at 100 Hz evoked both fast and slow excitatory synaptic currents (EPSCs) that were blocked, respectively, by DNQX, a non-N-methyl-d -aspartate receptor blocker, or atropine, a cholinergic muscarinic receptor (mAChR) blocker. Interestingly, many spontaneous-like, but stimulation-dependent, EPSCs, were seen for up to one second after the end of stimulation and were blocked by DNQX and decreased by EGTA-AM, a membrane permeable form of EGTA, showing they are glutamatergic EPSCs causing by asynchronous release of vesicular quanta. Moreover, application of atropine or carbachol, an mAChR agonist, caused, respectively, an increase in the number of asynchronous EPSCs or a decrease in the frequency of miniature EPSCs, showing that mAChRs mediated presynaptic inhibition of glutamatergic transmission of the PPTg onto NAergic A7 neurons. In conclusion, our data show direct synaptic transmission of PPTg afferents onto pontine NAergic neurons that involves cooperation of cholinergic and glutamatergic transmission. This dual-transmitter transmission drives the firing rate of NAergic neurons, which may correlate with axonal and somatic/dendritic release of NA. Highlights: The PPTg projects cholinergic and glutamatergic fibers to descending NAergic neurons. Cholinergic input exerts pre-/postsynaptic modulations by acting at M1/M3 receptors. Glutamatergic transmission features asynchronous release of a large number of quanta. This dual-transmitter system widens spiking window of NAergic neurons.